Selection of an Optimum Entropy Source Design for a True Random Number Generator. (2016) - Sreekumar, Lakshmi; Ramesh, P.
Abstract: Random number generators are a vital component in many cryptographic algorithms and systems, such as generation of keys in secret key cryptography and public key cryptography. For cryptographic applications, True Random Number Generator utilizes unpredictability as the key component. Insufficient entropy produces predictable keys, so the major concern is to have a better entropy source. Entropy source which is based on a delay chain structure is presented in this paper. Here the randomness is generated by the timing differential existing between the clock and the data signal. In this design the delays are adjusted so that the data can be sampled at the limit of switching point The proposed design is very simple as it is based on a loop structure which does not contain any complex structures like Delay Locked Loop (DLL).